Pengaruh Metode Pembelajaran dan Motivasi Berprestasi Terhadap Hasil Belajar Pendidikan Agama Islam Siswa SMKN 2 Ambon - Salim, Salim; Rusdi, M.; Isini, La; Ulfa, Siti Syahyidatul; Tinggapy, Hasanudin (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to analyze the influence of learning methods and achievement motivation on the learning outcomes of Islamic Religious Education (PAI). The method used in this research is a survey method with correlation analysis techniques. The approach used is a quantitative approach. Data was collected through questionnaires to measure learning methods and achievement motivation, as well as tests of PAI learning outcomes. The research sample was selected using a random sampling technique. Data analysis was conducted using multiple linear regression analysis. The analysis results show that there is a positive and significant relationship between the applied learning methods and student learning outcomes. The hypothesis test results indicate that at a 99% confidence level (α = 0.01), the multiple correlation coefficient (Ry₁₂) is 0.471. Thus, Ho is rejected and Hi is accepted, which means that there is a positive and highly significant influence of teacher personality competence and school culture together on student learning motivation. Further analysis reveals that a combination of effective learning methods and high achievement motivation has a greater impact on learning outcomes. This study emphasizes the importance of innovation in learning methods and strengthening student motivation to improve the quality of Islamic Education learning.